Robot Penyiram Tanaman Otomatis Berbasis App Inventor - Suwandi, Agus; Paronda, Abdul Hafid; Sujatmiko, Aeri (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2020)
The development of automation technology nowadays has allowed humans to do many things remotely, including daily activity such as watering plants. This study combines a mobile robot as a plant sprinkler and a smartphone as a remote control that uses Bluetooth as the connectors. Users can water plants remotely by using an application created with the App Inventor to control the Mobile Robot which is in charge of watering the field. Based on the test results, the sprinkler robot produces a current of 2 A and a voltage of 12 V with the heaviest water load that can be carried is 1 liter. The more water that is carried, the greater the measured voltage and current. The App Inventor application created successfully runs the sprinkler robot with an average delay of 1 second and the farthest distance is 5 m using a bluetooth module.